A simple unit root testing methodology that does not require knowledge regarding the presence of a break. Issue 3 (16th March 2018) - Sen, Amit
ABSTRACT: We develop a simple methodology that allows practitioners to test for the presence of a unit root without a priori knowledge regarding the occurrence of a break under the null hypothesis. We use a pre-test that is readily available in the estimated regression used to calculate the unit root statistics, and so our methodology is very easy to implement. The t -statistic corresponding to the impulse dummy variables evaluated at break date estimator is used as a pre-test to ascertain whether a break exists under the null hypothesis. Finite sample simulations show that our methodology yields tests that maintain their size.